Shadow of the northern giant: Russia's current and future engagement with the Indian Ocean Region - Muraviev, Alexey (Routledge, 2011)
In mid-September 2011, a Russian naval task force headed by the Udaloy-class destroyer, Admiral Panteleev, sailed across the Indian Ocean and commenced counter-piracy operations near the Bay of Aden. The sixth Russian Pacific Fleet task group had replaced a three-month deployment of the sister destroyer Severomorsk dispatched to the area from the Northern Fleet (Gavrilenko 2011, p. 1). The resumption of regular deployments of the Russian Navy to the area and Russia's active participation in counter-piracy operations is one of many examples of the country's current push to restore its fallen image and reputation in the Indian Ocean Region. In the past six years, Russia has intensified contacts with the region. However, questions remain as to the extent to which Russia will be involved in regional affairs. A majority of commentators remain sceptical of the country's interest and its capacity to play any significant future role in the Indian Ocean Region.